Mandatory Home Education During the COVID-19 Lockdown in the Czech Republic: A Rapid Survey of 1st-9th Graders' Parents - Brom, Cyril; Lukavský, Jirí; Greger, David; Hannemann, Tereza; Straková, Jana; Švaříček, Roman (Frontiers in Education, 2020)
Schools have been closed in many countries due to the on-going COVID-19 pandemic, but education continues online. Little is known about how parents cope with educating their children in this unprecedented situation. Here, we present the results of a rapid survey examining the experience of Czech parents of children in Grades 1-9 (Age 6-15; N = 9,810) with respect to home education home during the COVID-19 lockdown. This survey was distributed widely, but only online and parents participated voluntarily. Mainly families with an internet connection and interested in their children’s education (i.e., the majority of families with school-aged children in the Czech Republic) took part in the survey. The results show that these families tend to cope well with the current educational situation and view the overall schoolwork transferred to homes as useful. Most children spend 2-4 hours a day studying, while parents help them at least half the time. Parents mostly explain task instructions, check the work their children have done, and teach new topics. To a lesser extent, they help their children solve tasks. Teachers appear to assign tasks more often than they provide feedback and/or interact with children. Some parents face difficulties, but those are generally not severe. These include, most notably, a lack of time, issues with technologies, and inadequate teaching skills and content knowledge. Altogether, this work maps the current educational situation in a large segment of Czech families and highlights possible pitfalls to be avoided: in the Czech Republic and beyond.